Adverse Effect of Industrial Pollution on the Reproductive Outcome of Couples Living in and Around Bollarum and Patancheru Industrial Area - Tirumalaraju, Sridevi; Lakkaraju, Chandana; Puppala, Jharna; Kulathil, Dhanesh Mandam; Baluka, Vanitha; Prashanth, Chiliveri; Reddy, P.P. (International Journal of Scientific Research in Biological Sciences, 2019)
The effects of prolonged exposure to industrial pollutants and their spread in the environment results in development of diseases. Industrial pollutants can kill animals and plants, imbalance ecosystems and degrade man’s quality of life. Factory workers and people living near the areas with uncontrolled industrial pollution are especially vulnerable to health problems. Bollarum and Patancheru is one of the most important industrial areas in Hyderabad city of Telangana state. The present research aims to provide a further understanding about the adverse effects of industrial pollution on the reproductive outcome in couples who are living in and around this industrial area. Reproductive performance of 350 couples of this industrial area and 350 couples living away from the industrial area was studied. The frequencies of abortions, congenital malformations, still births, premature births and neonatal deaths were estimated. The analysis of the data showed an increase in the frequency of abortions, neonatal deaths, still births, congenital malformations, premature births and a decrease in the live births in the couples of industrial area compared to controls. The fertility rate of couples living in industrial areas also decreased in the controls in comparison in couples of industrial area. The adverse reproductive outcome of couples might be due to undue exposure to the industrial pollution. In order to reduce the effects of the Industrial pollution on man, the industries should take necessary action to treat industrial waste or gases before they are let in to the environment.